Moduli Space of 5/0-dimensional Complex Associative Algebras - Anderlik, Isaac; Loper, Michael; Picchiotino, Bryan; Tran, Thao (My University, 2014)
Algebraic structures are familiar objects of study for undergraduates in physics and mathematics. The purpose of this study was to classify all of the algebras on a 5/0 dimensional complex space.
Color poster with text and formulas.
Keywords: Associative algebras; Classification; Mathematical physics; Posters